The role of body build, strength and endurance abilities in achieving high results by rock climbers - Rokowski, R. (Journal of Kinesiology and Exercise Sciences, 2020)
Aim: the aim of this publication was to establish the importance of body build, strength and endurance abilities in achieving high results by climbers at higher elite/elite rock-climbing levels. Method: The study comprised 15 climbers with elite [n = 9] and higher elite [n = 6] training. The age of elite climbers was at an average of 33 years with SD = 8.2 years, and higher elite was, on average, x_ = 25.6 years, with SD = 7.6 years. The climbing efficiency was determined by the best RP and OS rock-climbing result in the last year. Selected somatic features were measured: body height, body mass, adipose tissue, upper limb length, circumferences of the forearm, arm, thigh and shank. Moreover, the following indices were calculated: Rohrer, slenderness and upper limb length. Finger strength was evaluated in the Grip-open 1 test. The absolute strength values were expressed per kg of body mass in the Grip-open 2 test. Fatigue resistance was measured in isometric contraction of the forearm muscles on a 2.5-cm hold - Hang 1, and 4-cm hold - Hang 2, while arm strength was assessed using the pull-up test. Results: Higher levels of the upper limb length index was noted among climbers at the highest rock-climbing compared to the elite group. Moreover, in all of the conducted motor tests, higher elite climbers scored better than those elite. In these trials, high correlation coefficients were reported between the results of motor tests and the results of RP and OS. RP - Grip-open 2 = 0.71, OS - Grip-open 2 = 0.70, RP - Hang 1 = 0.68, OS - Hang 1 = 0.72, RP - Hang 2 = 0.67, OS - Hang 2 = 0.73. The RP result was explained in 63% by the system of variables: finger strength plus fatigue resistance in isometric contraction on a larger slat. On the other hand, the OS result was explained in 77% by the same system of variables. Conclusions: Climbers with the highest rock-climbing level should have similar or even more favourable values of those somatic features considered significant than climbers representing the elite level. A high level of finger strength and fatigue resistance in isometric contraction of the forearm muscles significantly determines the effectiveness of climbing at higher elite/elite levels.